Generation Z in Responding to Communication Trends on Instagram - Syafrina, Annisa Eka (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This study aims to find out how Generation Z responds to communication trends on Instagram social media. Using qualitative research methods with a descriptive type, researchers conducted interviews with informants related to the research. The research results show that the emergence of communication trends on the social media Instagram has made the way Bhayangkara students use Instagram diverse. The emergence of communication trends on social media Instagram, does not make us have to follow it completely. Just like other media, the use of Instagram has both positive and negative impacts on its users. Many conveniences and information as well as entertaining content are presented on Instagram. However, not a little information on Instagram social media has a negative impact. So that students must be wiser in using social media.